Mediterranean Diet and White Blood Cell Count—A Randomized Controlled Trial - Álvaro Hernáez; Camille Lassale; Sara Castro-Barquero; Nancy Babio; Emilio Ros; Olga Castañer; Anna Tresserra-Rimbau; Xavier Pintó; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Ángel M. Alonso-Gómez; et al. (Foods, 2021)
We aimed to assess the effects of the antioxidant-rich Mediterranean diet (MedDiet) on white blood cell count. Our study population included participants in the PREvención con DIeta MEDiterránea study (average age 67 years old, 58% women, high cardiovascular risk). We assessed whether a MedDiet intervention enriched in extra-virgin olive oil or nuts, versus a low-fat control diet, modified the incidence of leukocytosis (>11 × 109 leukocytes/L), mild leukopenia (<4.5 × 109 leukocytes/L), or severe leukopenia (<3.5 × 109 leukocytes/L) in individuals without the condition at baseline (n = 3190, n = 2925, and n = 3190, respectively). We also examined whether MedDiet modified the association between leukocyte count alterations and all-cause mortality. Both MedDiet interventions were associated with a lower risk of developing leukopenia (incidence rates: 5.06% in control diet, 3.29% in MedDiet groups combined; hazard ratio [95% confidence interval]: 0.54 [0.36–0.80]) and severe leukopenia (incidence rates: 1.26% in control diet, 0.46% in MedDiet groups combined; hazard ratio: 0.25 [0.10–0.60]). High cumulative adherence to a MedDiet was linked to lower risk of leukocytosis (incidence rates: 2.08% in quartile 1, 0.65% in quartile 4; HRQ4-Q1: 0.29 [0.085–0.99]) and attenuated the association between leukopenia and all-cause mortality (P-interaction = 0.032). In brief, MedDiet decreased the incidence of white blood cell count-related alterations in high cardiovascular risk individuals.